Direct Written Corrective Feedback for Tenth Graders Recount Text: Adequate Practice to Boost Sentential Accuracy - Pooja Anggunsari; Sri Wahyuni (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Teaching writing is considered a complex skill to learn for EFL learners due to its difficulties. Many students and teachers in foreign countries need help to develop their students’ writing skills. Those can be solved by giving a technique that helps students develop ideas to write. One of the techniques is by using direct written corrective feedback. This study investigated the effectiveness of direct written corrective feedback in teaching writing recount text for the first-grade students in one Islamic Senior High School in Pare. Quasi-experimental research was used to determine the different scores between both classes after a treatment. Fifty-six (56) students participated in this study and were divided into two groups (experimental and control groups. The results were calculated using the Mann-Whitney U test since the data were not normal, and it was continued to find out the effect size to strengthen how far the influence of direct WCF was. The results revealed that direct WCF was effective at the medium level for the students’ writing accuracy. Implementing direct WCF for EFL students is suggested since it provides many benefits for teachers and students to boost writing accuracy.